Business Ethics in New Zealand Organisations: Views from the Middle and Lower Level Managers - Alam, Kazi Fioz (Journal of business ethics, 1999)
This study is carried out to assess the state of business ethics in New Zealand organisations from the point view of middle and lower level managers. The survey results clearly indicate that companies in New Zealand give low priorities to ethics with other values in the corporate culture. A significant number of respondents also believe that pressures from the top to achieve results and the organisational climate and ruthless competition help create an unethical environment. A greater emphasis on ethical content in the business curricula has been overwhelmingly supported by the respondents. Moreover, the majority of respondents also think that the ethical standard in New Zealand businesses has declined in the past decade., Finally, a number of suggestions have been put forward by the respondents to develop and maintain a high standard of ethical environment. These include mandatory moral/ethical education both in the educational institutions and in commerce and industry, commitment of top management and written and published code of ethics.